2003
DOI: 10.1108/02652320310479196
|View full text |Cite
|
Sign up to set email alerts
|

Strategy, competition and diversification in European and Mexican banking

Abstract: This article identifies whether top managers in banks’ parent companies are highly involved in the design of strategy and examines how management styles influence (or reflect influences) on diversification decisions within bank markets. Alongside this assessment, the research ranks the main concerns to design strategy in banking within an international setting (including the role of information and telecommunication technologies in the design and implementation of banks’ diversification strategies). Results em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Parnell (2010) observed that a strategy can be distinguished as cost leadership or differentiation strategy. In recent years, researchers have started taking an interest in strategy from the banking perspective (Bapat & Mazumdar, 2015;Batiz-Lazo & Wood, 2003;Pleshko, 2007;Pleshko, Peev, & Heiens, 2014). There is a need to investigate which strategic orientation is placed in higher importance for performance.…”
Section: Introductionmentioning
confidence: 99%
“…Parnell (2010) observed that a strategy can be distinguished as cost leadership or differentiation strategy. In recent years, researchers have started taking an interest in strategy from the banking perspective (Bapat & Mazumdar, 2015;Batiz-Lazo & Wood, 2003;Pleshko, 2007;Pleshko, Peev, & Heiens, 2014). There is a need to investigate which strategic orientation is placed in higher importance for performance.…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that banking managers need to adopt a genuinely customer-focused mindset if the bank is to become truly market-oriented. Notably, the understanding of data usage and technology is crucial during digital transformation to avoid Bátiz Lazo and Wood (2003) finding that the lack of understanding of new opportunities might hold back development.…”
Section: Discussionmentioning
confidence: 99%
“…One interviewee summarized, contr While the study data implied that the digital transformation in banking emphasizes mobile channels, the consequences do not seem to be clear. Bátiz Lazo and Wood (2003) find that there is a risk in the prevailing bank management style. They argue that senior management's lack of understanding of new opportunities and consequences might hold back development or lead to the pursuit of inappropriate growth opportunities.…”
mentioning
confidence: 99%
“…In the course of the last three decades of the twentieth century banks increasingly relied on applications of IT for more than gaining greater efficiency in everyday business, and "engineers" and "bankers" fought for control of the organization (Fincham et al, 1994). This arm wrestling prevailed until "hybrids" or people that could be trusted and also thoroughly "speak" the language of both banking and engineering rose through the ranks and came to dominate banking organizations in the late 1990s (Bátiz-Lazo and Wood, 1999Wood, , 2003.…”
Section: <Table 1 About Here>mentioning
confidence: 99%